Analisis Penentuan Komoditas Unggulan Sektor Pertanian dalam Pengembangan Wilayah: Studi Kasus di Kecamatan Bayah Kabupaten Lebak - Selfi Nor Amalia Istiqomah; Mujio Mujio; Janthy T Hidayat (Pelantar Press, 2024)
Regional development is a partial or comprehensive movement to improve the function of land and the structuring of social, economic, cultural, educational, and welfare of the community to advance the region. The importance of commodities in regional development is closely related to key factors such as economic growth, increase in farmers' income, food security, infrastructure development, economic diversification, natural resource management, increasing competitiveness, and strengthening institutions and policies, all of which contribute to community welfare and environmental sustainability. The goals of superior commodities are to increase local economic growth, increase farmers' incomes, achieve food security, encourage infrastructure development, diversify the economy, manage natural resources sustainably, increase competitiveness in the market, and strengthen institutions and policies that support the agricultural sector. Therefore, it is necessary to research the development of superior commodities in Bayah District with the research title